IMPROVING SCIENCE LITERACY SKILLS USING THE DEVELOPMENT OF LKPD BASED ON THE PROBLEM BASED LEARNING (PBL) MODEL IN ELEMENTARY SCHOOL STUDENTS - Tamam, Abdulloh; Suryanti; Sudibyo, Elok (Universitas Negeri Jakarta, 2023)
Indonesia's ranking related to scientific literacy has not experienced a significant increase. In fact, in facing increasingly difficult challenges in the 21st century, students must have literacy skills. The importance of scientific literacy skills in education makes scientific literacy a standard measure of the quality of education. This study aims to determine the effect of learning using the problem-based learning model-based LKPD development on elementary students' scientific literacy abilities. This research is included in the experimental research. A sample of 27 elementary school students class V B SDN 147 Gresik. This research was conducted in March-May 2023 at SDN 147 Gresik. Scientific literacy skills were carried out 2 times, namely pretest and posttest. Based on the normality test, it was found that the value was < 0.05, indicating that the data distribution was not normal. The results of the Wilcoxon signed ranks test obtained a significance value of P of 0.000 < 0.05. The conclusion obtained is that there is an effect of learning using the problem-based learning model-based LKPD development on the scientific literacy abilities of elementary students. Subsequent studies require LKPD research based on problem-based learning models on other elementary learning materials.